2016
DOI: 10.7759/cureus.849
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hope and Resilience on Multiple Factors in Neurosurgical Patients

Abstract: The purpose of the present article is to outline and review the impact of stable psychological characteristics on the emotional and functional outcomes of neurosurgical patients. Neurosurgical patients face adversity as inherent to their diagnoses and, consequently, experience emotional distress. Despite commonalities in diagnoses, diverse outcomes are seen post-neurosurgery, which are influenced by psychological factors. Therefore, an understanding of neurosurgical patients’ behavior, thoughts, and feelings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 50 publications
3
45
1
Order By: Relevance
“…Hope is described as an optimistic attitude of mind based on an expectation of positive outcomes. Studies have found that hope is positively correlated with life satisfaction and serves as a buffer against the impact of negative and stressful life events [25]. It has been discovered in studies that family members can help induce hope in severely ill patients, and that this alone can help the affected patient to push on and get better [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hope is described as an optimistic attitude of mind based on an expectation of positive outcomes. Studies have found that hope is positively correlated with life satisfaction and serves as a buffer against the impact of negative and stressful life events [25]. It has been discovered in studies that family members can help induce hope in severely ill patients, and that this alone can help the affected patient to push on and get better [26].…”
Section: Discussionmentioning
confidence: 99%
“…This can be applied to the patients in this study as well, both that they had a deep sense that things will get better, but also that they realized that their friends and family wanted them to get better and wanted them to lose su cient weight to get on the transplant list. It is clear that hope is important and necessary to overcome di culties in life [25].…”
Section: Discussionmentioning
confidence: 99%
“…In explaining this nding, it can be said that due to the fact that abortion due to fetal malformation is one of the factors threatening the physical and mental health of women, causes them to endure a lot of stress, sadness and grief and suffer in effective adjustment and coping. The researches have consistently shown that people with positive resilience-related traits are able to manage and overcome the unfortunate problems of life (47) so by increasing women's support and awareness of abnormal fetuses, and screening and diagnostic methods, post-abortion care, contraceptive methods, and resilience skills education, it may lead to reduced stress and increased quality of life associated with improving their resilience, which is effective on both their mental health and the process of physical recovery and helps for the preparation for repregnancy. In the meantime, social network education is one of the best strategies that can increase the level of awareness of women and provide them with the necessary information.…”
Section: Discussionmentioning
confidence: 99%
“…In those previously diagnosed with a condition, the ability to adhere to prescribed health behaviors or regimes are key in experiencing positive changes or maintaining well-being in the face of chronic illness (Osterberg and Blaschke, 2005). Additionally, the maintenance of positive outlook is key in fostering resilience and well-being despite adversities, such as impending surgery or chronic illness (Duggal et al., 2016). Finally, the availability of social support has been linked to lower rates of morbidity and mortality, and thus has been suggested to buffer against detrimental health outcomes throughout the lifespan (Uchino, 2006).…”
Section: Introductionmentioning
confidence: 99%